Structural Changes in Agriculture in the Pomurje Region After 1991 - Kraner , Matej; Lorber, Lučka (Journal for Geography, 2010)
The Pomurje region is the most agricultural and the least developed region in Slovenia. Since 1991, the year when Slovenia gained its independence, the country transformed from the socialist system to the free market capitalism and was forced to restructure the agricultural policy. The decrease and the aging of the population, the abandon of the agriculture production and the decay of cultural landscape turned out to be serious problems. In Pomurje, agriculture was faced with unfavourable age structure of farmers in family farms. The Slovene agricultural policy was aware of this problem and took a number of measures to encourage the aging farmers to retire and the young generation to take over. Alongside this process began the process of merging land in the Pomurje rural areas. In the last 10 years, the agriculture in Pomurje underwent the improvement of agricultural technology, the specialization of productions and the enlargement of farms.
Keywords: Slovenia; Prekmurje; agricultural policies; CAP; agricultural structure; agricultural development